Expression, polymorphism of IRF5 gene and association with serum cytokine levels in pig. Issue 3 (3rd July 2018) - Liu, Yang; Xie, Rui; Li, Hejun; Hu, Zhengzheng; Wang, Shiwei; Yin, Zongjun
Abstract: Interferon regulatory factor 5 (IRF5) gene is a crucial transcription factor in immune system and has shown its functionally diverse roles in the regulation of antiviral responses. Previous study revealed the IRF5 gene resides in the reported quantitative trait locus (QTLs) for cytokine levels. In this report, the porcine IRF5 gene was selected to investigate its effect on cytokine level in serum. The mRNA expression of IRF5 was also detected by real time quantitative PCR and the results revealed that IRF5 mRNAs were widely expressed in all analysed tissues except muscle. A genomic variant (g.10764 T > C) in exon 7 of the IRF5 gene was identified by direct sequencing, and then the SNP was genotyped by MALDI-TOF MS assay method in three pig populations. The further association analysis indicated that the SNP was significantly associated with the level of interferon-γ (day 20), interleukin 10 (day 35) and ratio of interferon-γ/interleukin 10 (day 35) in serum ( p  < .05). An interferon known to be key in immune processes. These results suggested that IRF5 could serve as a promising candidate gene for pig disease resistance breeding.